SHOPPING EXPERIENCE AND CUSTOMER REVIEWS ON SHOPPING LOYALTY ON SHOPEE E-COMMERCE Case study in Kersik Tuo Village Kayu Aro Subdistrict, Indonesian - Budaya, Indra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study examines the effect of shopping experience and customer reviews on shopping loyalty in Shopee e-commerce, with a case study in Kersik Tuo Village, Kayu Aro District. In the era of globalisation and the rapid development of information technology, e-commerce is becoming an important platform for trading activities. Customer loyalty is defined as a consumer's commitment to shop repeatedly on a particular site. The research method used is a survey with a quantitative approach, involving 60 respondents selected by purposive sampling. The results of multiple linear regression analysis show that both shopping experience and customer reviews have a positive and significant influence on shopping loyalty. These findings indicate the importance of marketing strategies that focus on improving consumer experience and review quality to build customer loyalty on e-commerce platforms.